Development of a Modular Prototype of Vital Signs Monitor for Critical Patients - Hernández Guevara, Leopoldo; Pimentel Hernández, Karen S. (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Advances in the design of vital signs monitors are verified in the improvement of components, transmission and storage in databases, however, the operating principle remains similar to the original. It is a fact that developing countries have been consumers of technology, with little development in the field of design. This research deals with the development of a vital signs monitor prototype and its validation; using specific accessible components and modular designs for its design, identifying the future challenges of design in the health area in our country.